Measurement properties of PROMIS short forms for pain and function in total hip arthroplasty patients - Anika Stephan; Vincent A. Stadelmann; Michael Leunig; Franco M. Impellizzeri (SpringerOpen, 2021)
Plain English summary Measurement qualities of PROMIS instruments are mainly assessed for computer adaptive testing but not for non-adaptive short questionnaires. As these questionnaires are in use, their measurement properties must also be evaluated. Results from computer adaptive testing cannot simply be transferred. We studied the measurement qualities of the German PROMIS short questionnaires for pain intensity, pain interference and physical function in patients undergoing hip replacement. We wanted to see how these questionnaires perform when compared to the Oxford Hip Score, a standard questionnaire commonly used to test hip-related disability in these patients. The three questionnaires can be considered acceptable for use in hip replacement patients, but some limitations do exist. Patient improvement in physical function might be underestimated because many patients reach the highest possible score and further improvements cannot be measured. Also, any small but important improvement in physical function cannot be distinguished from measurement error in individual patients.